2017
DOI: 10.1007/s10549-017-4552-6
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 deficiency is a recurrent event in early-onset triple-negative breast cancer: a comprehensive analysis of germline mutations and somatic promoter methylation

Abstract: BRCA1 deficiency was recurrent in early-onset triple-negative breast cancer in Brazilian patients and associated with improved survival. With the new treatment modalities being investigated, including poly (ADP-ribose)-polymerase (PARP) inhibitor therapy, our results suggest that a significant proportion of young women with this subtype of tumor might benefit from PARP inhibitor treatment, which warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 52 publications
5
38
0
2
Order By: Relevance
“…Enduring efforts made by researchers or organizations such as CIMBA demonstrate the ubiquitous perception of higher ratio of BRCA mutations in younger patients with more aggressive subgroups of breast cancer. 223 , 225 , 226 , 227 Nonetheless, the majority of these studies imply a comparable outcome among patients regardless of BRCA status, limiting the application of BRCA mutation status in prognosis prediction.…”
Section: Cancer Gene Mutations In Breast Cancermentioning
confidence: 99%
“…Enduring efforts made by researchers or organizations such as CIMBA demonstrate the ubiquitous perception of higher ratio of BRCA mutations in younger patients with more aggressive subgroups of breast cancer. 223 , 225 , 226 , 227 Nonetheless, the majority of these studies imply a comparable outcome among patients regardless of BRCA status, limiting the application of BRCA mutation status in prognosis prediction.…”
Section: Cancer Gene Mutations In Breast Cancermentioning
confidence: 99%
“…17,18 It has been suggested that promoter methylation in tumor DNA might be a mechanism of inactivation of BRCA1 gene in triple-negative BC (TNBC) patients. 19,20 In the present study, we evaluated the association of BRCA1 methylation in blood-derived DNA with the risk of BC, including TNBC. In addition, we analyzed methylation in paired tumor samples and assessed the degree of concordance between methylation in blood and breast tumor tissue.…”
Section: Introductionmentioning
confidence: 99%
“…About 75% of BC which arise in women who carry germline BRCA1 mutations are triple‐negative; however, only about 10% of patients with triple‐negative breast tumors have BRCA1 mutations . It has been suggested that promoter methylation in tumor DNA might be a mechanism of inactivation of BRCA1 gene in triple‐negative BC (TNBC) patients …”
Section: Introductionmentioning
confidence: 99%
“…DNA promoter hypermethylation could be an alternative mechanism of inactivating BRCA1. BRCA1 promoter hypermethylation has been reported in 16-57% of TNBCs across studies [14][15][16][17][18][19][20] , superseding the frequency of germline BRCA1 alterations, however, with conflicting reports about association with prognosis (e.g. refs.…”
mentioning
confidence: 99%